Branchial Fistula : A Case Report (TAJ: Journal of Teachers Association, 2018)
We report a case of complete branchial fistula in a 13-year-old boy which could be evaluated by a contrast study. The tract was completely excised and the patient had an uneventful recovery. Branchial fistulae are formed due to the persistence of the embryonic second branchial cleft. Complete fistulae with the internal opening in the region of the tonsillar fossa are not common and should be properly evaluated before going to surgical exploration.TAJ 2011; 24(2): 145-147